BK-UM in patients with recurrent ovarian cancer or peritoneal cancer: a first-in-human phase-I study. Issue 1 (December 2017) - Miyamoto, Shingo; Yotsumoto, Fusanori; Ueda, Taeko; Fukami, Tatsuya; Sanui, Ayako; Miyata, Kohei; Nam, Sung; Fukagawa, Satoshi; Katsuta, Takahiro; Maehara, Miyako; Kondo, Haruhiko; Miyahara, Daisuke; et al.
Abstract Background BK-UM (CRM197) is a mutant form of diphtheria toxin and a specific inhibitor of heparin-binding epidermal growth factor-like growth factor (HB-EGF). We assessed the safety, pharmacokinetics, recommended dose, and efficacy of BK-UM in patients with recurrent ovarian cancer (OC) or peritoneal cancer (PC), and measured HB-EGF levels in serum and abdominal fluid after BK-UM administration. Methods Eleven patients with advanced or recurrent OC or PC were enrolled and treated with BK-UMvia the intraperitoneal route. The dose was escalated (1.0, 2.0, 3.3, and 5.0 mg/m2 ) using a 3 + 3 design. Results Eight of 11 patients completed treatment. No dose-limiting toxicity (DLT) was experienced at dose levels 1 (1.0 mg/m2 ) and 2 (2.0 mg/m2 ). Grade 3 transient hypotension as an adverse event (defined as a DLT in the present study) was observed in two of four patients at dose level 3 (3.3 mg/m2 ). Treatment with BK-UM was associated with decreases in HB-EGF levels in serum and abdominal fluid in seven of 11 patients and five of eight patients, respectively. Clinical outcomes included a partial response in one patient, stable disease in five patients, and progressive disease in five patients. Conclusions BK-UM was well tolerated at doses of 1.0 and 2.0 mg/m2, with evidence for clinical efficacy in patients with recurrent OC or PC. A dose of 2.0 mg/m2 BK-UM is recommended for subsequent clinical trials. Trial registration This trial was prospectively performed as an investigator-initiated clinical trial. The trial numbers areUMIN000001002 and UMIN000001001, with registration dates of 1/30/2008 and 2/4/2008, respectively. UMIN000001001 was registered as a trial for the continuous administration of BK-UM afterUMIN000001002 .